Local interpretations on malaria and the discourse on the traditional health care providers in southern Mozambique - Sequeira, A. R. S. (2017)
The narratives on the diagnosis and causes of malaria are diverse and apparently ambiguous, being based beyond the body, on the social relations among peers, their ancestors, and nature. Based on a qualitative study and a four-year stay in Mozambique, this article analyzes the discourses of patients and biomedical practitioners on traditional health care providers, i.e., tinyanga and zion pastors, linking them to local terminology of malaria, in a rural district in southern Mozambique. In the current context of therapeutic pluralism and high mobility, the lack of solidarity and compassion attributed to tinyanga is supported by the monetization and commodification of their medicinal rituals and knowledge, as well as by competition with other providers in attracting patients. The implementation of zion churches, of Christian nature and performing therapeutic practices similar to tinyanga, is presented as a local advantageous solution due to the strong community connection, the comfort and reciprocity among the members, and the therapeutic results at low cost. In terms of health care policies and clinical practice, the invisibility of zion pastors and the subordinate role of healers is managed according to interests, based on vague ideas and prejudices from biomedical providers. The implementation of health policies that address the local diversity, the existing power relations and medical knowledge and practices can strengthen the biomedical care services and harmonize relations between the providers and the population.